Peramalan BI Rate Di Indonesia dengan Metode Time Series Model ARIMA - Hasanah, Uswatun (Fakultas Ekonomi dan Bisnis Islam, 2023)
Bi rate determination is one of the monetary policies carried out by the government to regulate the macroeconomic level. The determination of the Bi rate serves as one of the references for entrepreneurs in determining steps for business sustainability. In addition, determining the Bi rate can also control inflation by regulating the amount of money circulating in the community. This research implements the ARIMA model to forecast the BI rate in the period December 2023 to April 2024. Based on the results of the tests that have been carried out, using the best variable values, namely comparing AIC, SIC and HQC values in determining the best model, the ARIMA model (1,1,0) was chosen. The results of the forecasting value in this study that the Bi Rate for the next 5 months, starting from December 2023 to April 2024, shows a downtrend in the Bi rate value